Discourse of the collective subject: conceptual foundations, approaches, and applications in qualitative research - Genaro, Luís Eduardo [UNESP]; Marconato, José Victor; Pinotti, Felipe Eduardo [UNESP]; Valsecki Júnior, Aylton [UNESP]; Adas Saliba, Tânia [UNESP]; Lopez Rosell, Fernanda [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2024)
Due to its qualiquantitative approach, the Discourse of the Collective Subject (DCS) stands out as a methodology of great importance in research focused on public health, enabling comprehensive analyses, both qualitative and quantitative, based on the collected data. The purpose of this article is to present the theoretical foundation and applicability of DCS for the development and analysis of qualitative research. In the text, the concepts of discourse and analysis are discussed, establishing a relationship with the DCS analysis methodology. The use of this methodology is appropriately revealed through qualitative data, grounded in the Theory of Social Representation, which has the capacity to unveil thoughts, representations, values, and beliefs of a community about a specific theme, employing scientific methods. We believe that this study invites the reader to reflect on the methodological aspects of the DCS, presenting relevance as an instrument or practical tool in the context of qualitative research.
Discurso do sujeito coletivo: bases conceituais, enfoques e aplicações em pesquisas qualitativas
Keywords: Discourse of the Collective Subject; Methods; Qualitative research; Theory of Social Representations